A tőzsdei bevezetés jelentősége két magyar óriásvállalat példáján - MOL és MVM - Péter Mihályi; Éva Sztankó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
– The Hungarian oil company (MOL) and the national electricity holding (MVM) counted as the largest socialist enterprises already 30 years ago. Prior to 1990, they were roughly of the same size in respect of sales and employment, as well. Since the regime change, however, their development paths differed enormously. MOL has become an internationally listed company, one of the largest in its kind in Central and Eastern Europe, but remained strongly under the control of its Hungarian top management. By contrast, MVM remained fully state-owned, in spite of the partial privatisation in 1996. The electricity company failed to become international, never became mature enough for an IPO. As a result, the company actually shrank both in absolute and even more in relative terms. In terms of sales, MOL is now six times bigger. This paper argues that the explanation of this divergence is to be found in the different values and strategies of the two companies' top management. The leaders of the electricity industry have continued to apply the enginering logic of the centrall planned economy even after 1990. Their main contention was that this is a "particular" industry, which requires long-term plans and close cooperation with the incumbent governments. The management of MOL, by contrast, has thought in terms of money and capital right from the regime change. As business people, they quickly understood that the success of MOL is critically dependent on its integration into the globalized world, which in practice meant agressive expansion abroad. The leaders of MVM instead tried to hamper the privatization process all along. The managers of MOL have also understood that privatization through an IPO is the appropriate trick to maximize their own, internal power. Furthermore, they also grasped that through stock options they can become Hungarian billionaires themselves.
Keywords: L1; L5; L71; P26; 330; IPO; motivation of firm managers; electricity industry; Hungarian oil and gas industry